TECRL, a new life‐threatening inherited arrhythmia gene associated with overlapping clinical features of both LQTS and CPVT - Harsha D Devalla; Roselle Gélinas; Elhadi H Aburawi; Abdelaziz Beqqali; Philippe Goyette; Christian Freund; Marie‐A Chaix; Rafik Tadros; Hui Jiang; Antony Le Béchec; Jantine J Monshouwer‐Kloots; Tom Zwetsloot; et al. (EMBO Molecular Medicine)
Abstract Genetic causes of many familial arrhythmia syndromes remain elusive. In this study, whole‐exome sequencing (WES) was carried out on patients from three different families that presented with life‐threatening arrhythmias and high risk of sudden cardiac death (SCD). Two French Canadian probands carried identical homozygous rare variant in TECRL gene (p.Arg196Gln), which encodes the trans‐2,3‐enoyl‐CoA reductase‐like protein. Both patients had cardiac arrest, stress‐induced atrial and ventricular tachycardia, and QT prolongation on adrenergic stimulation. A third patient from a consanguineous Sudanese family diagnosed with catecholaminergic polymorphic ventricular tachycardia (CPVT) had a homozygous splice site mutation (c.331+1G>A) in TECRL. Analysis of intracellular calcium ([Ca2+]i) dynamics in human induced pluripotent stem cell‐derived cardiomyocytes (hiPSC‐CMs) generated from this individual (TECRLHom‐hiPSCs), his heterozygous but clinically asymptomatic father (TECRLHet‐hiPSCs), and a healthy individual (CTRL‐hiPSCs) from the same Sudanese family, revealed smaller [Ca2+]i transient amplitudes as well as elevated diastolic [Ca2+]i in TECRLHom‐hiPSC‐CMs compared with CTRL‐hiPSC‐CMs. The [Ca2+]i transient also rose markedly slower and contained lower sarcoplasmic reticulum (SR) calcium stores, evidenced by the decreased magnitude of caffeine‐induced [Ca2+]i transients. In addition, the decay phase of the [Ca2+]i transient was slower in TECRLHom‐hiPSC‐CMs due to decreased SERCA and NCX activities. Furthermore, TECRLHom‐hiPSC‐CMs showed prolonged action potentials (APs) compared with CTRL‐hiPSC‐CMs. TECRL knockdown in control human embryonic stem cell‐derived CMs (hESC‐CMs) also resulted in significantly longer APs. Moreover, stimulation by noradrenaline (NA) significantly increased the propensity for triggered activity based on delayed afterdepolarizations (DADs) in TECRLHom‐hiPSC‐CMs and treatment with flecainide, a class Ic antiarrhythmic drug, significantly reduced the triggered activity in these cells. In summary, we report that mutations in TECRL are associated with inherited arrhythmias characterized by clinical features of both LQTS and CPVT. Patient‐specific hiPSC‐CMs recapitulated salient features of the clinical phenotype and provide a platform for drug screening evidenced by initial identification of flecainide as a potential therapeutic. These findings have implications for diagnosis and treatment of inherited cardiac arrhythmias.